Preference shares: analysis of Sharīʿah issues - Shamsiah Mohamad; Mezbah Uddin Ahmed; Mohd Bahroddin Badri (ISRA International Journal of Islamic Finance, 2017)
Purpose: The purpose of this paper is to analyze the different features of preference shares from accounting and Sharīʿah perspectives. It also aims to study Sharīʿah issues arising from preference shares and to subsequently propose solutions for identified issues that will help in structuring Islamic preference shares. Design/methodology/approach The paper uses a qualitative method by analyzing relevant documents and literature to understand the subject matter and Sharīʿah-related issues. Findings The paper finds that several features of conventional preference shares, such as capital guarantee, loss sharing disproportionate to capital contribution, fixed profit, profit guarantee and waiver of rights before realization of profit, make them a Sharīʿah non-compliant instrument. Research limitations/implications The paper is conceptual in nature; however, it provides directions for future empirical research. Originality/value The paper provides a practicable solution to structure Sharīʿah-compliant preference shares.
Keywords: 330; capital guarantee; debt; Equity; liability; preference shares